Standardized development objects reconstruction in difficult geoclimatic conditions - Valerievich Radionov, Timur (Journal of Architecture and Urbanism, 2014)
In the article the strategic reconstruction issues of standardized development objects that are in the difficult geo-climatic conditions are examined. The solution of such issues depends on the demographic, social and economic position of the considered locality. During the research basic tasks were set that are aimed at the investigation of geological conditions of the area, the detailed analysis of the typological characteristics of buildings and structures that are undergoing the reconstruction as well as taking into account legislative environment of the project activities in this direction. Researches conducted, tasks set and recommendations developed have given the opportunity to present the main results of researches and to formulate definite conclusions. Scientific novelty of the research lies in the development of scientific and practical recommendations concerning the reconstruction of standardized development objects which are located in the difficult geoclimatic conditions.